Hybrid multilevel modelling of axial permanent magnet drivers. (October 2018) - Shi, Songning; Wang, Dazhi
Abstract: A five-layered analytical model of axial permanent magnet drivers that considers the permanent magnet back iron, the permanent magnet array, the air gap, the copper, and the copper back iron is presented. The multilayer boundary value problem is solved and a simple torque expression represented by the Fourier series is derived. A permanent magnet array optimisation method is proposed based on this novel idea. The results achieved are compared with the results of the finite element method and measurements which confirms that our proposed analytical method is more effective.